2020
DOI: 10.1136/svn-2020-000624
|View full text |Cite
|
Sign up to set email alerts
|

Transradial versus transfemoral access for anterior circulation mechanical thrombectomy: analysis of 375 consecutive cases

Abstract: ObjectiveTo compare transradial artery access (TRA) to the gold standard of transfemoral artery access (TFA) in mechanical thrombectomy (MT) for stroke caused by anterior circulation large vessel occlusion.MethodsThe clinical outcomes, procedural speed, angiographic efficacy and safety of both techniques were analysed in 375 consecutive cases over an 18-month period in a high volume statewide neurointerventional service.ResultsThere was no significant difference in patient characteristics, stroke parameters, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
(15 reference statements)
1
22
0
Order By: Relevance
“…There were two (0.67%) reported access-site complications among the transradial group, whereas there were 27 (5.8%) in the transfemoral group. The frequency of symptomatic ICH reported in three studies [13][14][15] and our case series was 4.78% in the transradial group and 8.06% in the transfemoral group. Successful reperfusion was achieved in 88.8% of the transradial group and 93.2% of the transfemoral…”
Section: Transradial Versus Transfemoral Analysissupporting
confidence: 41%
See 2 more Smart Citations
“…There were two (0.67%) reported access-site complications among the transradial group, whereas there were 27 (5.8%) in the transfemoral group. The frequency of symptomatic ICH reported in three studies [13][14][15] and our case series was 4.78% in the transradial group and 8.06% in the transfemoral group. Successful reperfusion was achieved in 88.8% of the transradial group and 93.2% of the transfemoral…”
Section: Transradial Versus Transfemoral Analysissupporting
confidence: 41%
“…Phillips et al reported 3-month mRS scores of 0-2 for only those TRA and TFA groups of patients who had premorbid mRS scores of 0-2. 15 Therefore, functional outcomes were not reported for eight patients in the TRA group and 31 patients in the TFA group. Due to the lack of complete data, a pooled analysis was not possible.…”
Section: Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…It suggests that using TRA for anterior circulation MT may be fast, effective, safe and not inferior to the TFA. 83 However, there are several limitations of TRA: (1) it may not use a larger diameter of neurointerventional access catheter or a BGC; (2) difficulty to navigate through sharp turns or anatomy, that is, the acute angle between the carotid artery and subclavian artery in the aortic arch, the occlusion of the subclavian artery and varies types of aortic arch; and (3) require addition training.…”
Section: Ais With Intracranial Arterial Atherosclerosismentioning
confidence: 99%
“…The median (IQR) catheterization time was 10 (8-16) min in the direct TRA group and 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in the direct TFA group (P < 0.001) (Fig. 3A).…”
Section: Catheterization Timementioning
confidence: 99%